2018
DOI: 10.1177/1049909118792871
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Religious Characteristics and Their Perceptions of the Psychological Impact of Patient Prayer and Beliefs at the End of Life: A National Survey

Abstract: US physicians hold divided perceptions of the psychological impact of patients' religious beliefs/practices at the end of life, although they more are likely to believe that frequent prayer has a positive psychological impact for patients. Formal training in spiritual care may significantly improve the number of religion/spirituality conversations with patients at the end of life and help doctors understand and engage patients' religious practices and beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In addition to the three most prominent themes, processing death and existential anxiety was a highly recurring theme, even though this study did not specifically target patients with terminal illness or in hospice care. This pattern corresponds with existing literature that thoughts of death and dying are more prevalent in the minds of older patients than the frequency with which physicians address such existential concerns (Thompson 2019). A recent 2020 cohort study following 261 palliative care patients through anonymous questionnaires found that 62% of patients identified at least one spiritual concern and 32% of patients mentioned fear of dying (Michael et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In addition to the three most prominent themes, processing death and existential anxiety was a highly recurring theme, even though this study did not specifically target patients with terminal illness or in hospice care. This pattern corresponds with existing literature that thoughts of death and dying are more prevalent in the minds of older patients than the frequency with which physicians address such existential concerns (Thompson 2019). A recent 2020 cohort study following 261 palliative care patients through anonymous questionnaires found that 62% of patients identified at least one spiritual concern and 32% of patients mentioned fear of dying (Michael et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…"Secure attachment to God" has been shown to improve personal well-being measures at the end of life (Bradshaw and Kent 2018). Contrary to colloquial belief in God's presence has been associated with an increased likelihood of DNR status by improving one's "coming to terms" with death (Sulmasy 2006;Thompson 2019). In our study, God's presence was mentioned in questionnaire responses alongside the clinical themes of physical healing, physical limitations, and events of death or terminal illness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations